A Research on CEO Branding - Büşra Çetin; Neslihan Özmelek Taş; Emet Gürel; Azra Kardelen Nazlı (Türkiye İletişim Araştırmaları Dergisi, 2023)
“Personal branding” is a phenomenon that has attracted attention since it was first introduced by Tom Peters (1997). Starting from the assumption that every person is a “brand” with a value proposition, the concept of personal brand has expanded its scope over time and has created its own sub-types. The CEO brand is one of these subtypes. CEO branding means that the CEO can brand just like a product, service or institution. In this study, personal brand concepts and practices are analyzed on the axis of the CEO brand and on the basis of new media. The study was designed with a qualitative research method and was carried out using descriptive analysis. The sample of the research consists of CEO accounts that have accounts on LinkedIn. The sample of this study consists of 20 CEOs selected among “Turkey’s 50 Most Admired CEOs” who were awarded the Golden Leader Awards in 2021 as a result of the research conducted by KREA. It is desired to explain the CEO brand through the analysis themes of the study. It is aimed to explain the CEO brand through the analysis themes of the study. These themes, adapted from İbicioğlu et al. (2014) are; image management, differentiation, positioning, and career interest become prominent as the main themes of the study. The sub- themes of the study were examined in detail as contextual richness, personal and professional development, personal qualities, distinctiveness, professional photographs, professional achievements and positive features,professional abilities, professional titles and duties, professional competence, and future goals. The aim of this study is to examine personal brand practices, CEO brands’ use of new media within the scope of the determined sample and research, and to explain the appearance of CEO brands in new media in the context of personal brand with a descriptive analysis. With this analysis, it is aimed to provide a conceptual framework to the literature on the use of LinkedIn by CEO brands. Thus, it was desired to create a scope and definition area for personal branding and CEO branding, which is a relatively new topic in the field of communication studies. The methodology of this research is descriptive content analysis, which belongs to the qualitative research design. The qualitative data analysis program MAXQDA was used to evaluate the research data. Within the scope of the study carried out over MAXQDA, it has been determined that CEOs use new media effectively and carry out branding activities through new media. It has been found that this situation makes a positive contribution to the personal brands of CEOs and the brands of the institutions they work for. In other words, the results of this study create a sustainable CEO brand concept by displaying personal qualities parallel to the personal images of CEO brands and the images of institutions. It has been observed that the definition and scope of the CEO brand concept, the CEO branding process, and the vital importance of new media in the CEO branding process are as discussed in the literature.